Hubungan Antara Kesepian Dengan Kecenderungan Agresivitas Pada Remaja - Anggara, Ricky Harcahya, Rini Lestari, M.Si (2016)
The purpose of this study is : 1). To know a correlation between loneliness with aggressiveness tendency among adolescents. 2). To know the lonely effective contribution of aggressiveness tendency . 3). To know the level of loneliness in adolescents. 4). To know level of aggressiveness tendency among adolescents. The hypothesis is that there is a positive correlation between loneliness and aggressiveness tendency. The subjects were 104 subjects. The instrument were 15-18 years old who live in District Banjarsari Surakarta. These studies use quantitative methods, which the loneliness variable is an independent variable and the dependent variable is aggressiveness tendency. As for the measuring instrument that used in this research are: a). Scale of loneliness and b). The scale of the aggressiveness tendency. The data analysis techniques that used in this research is product moment correlation. The result were positive correlation between loneliness and aggressiveness tendency among adolescents in Surakarta. The higher the loneliness then the higher aggressiveness tendency, conversely the lower loneliness the lower aggressiveness tendency. This is indicated by the value of r = 0.420 with sig. 0, 000; (P <0.01). level relatively low of loneliness for subject. Aggressiveness tendency on the subject is low. This is demonstrated by the empirical mean of 43.91, while the average hypothetical 55. effective contribution (SE) loneliness amounted to 17.64%. It shows there are still 82.36% of other variables that can aggressiveness tendency variables outside loneliness variable. Keyword : Aggressiveness, Loneliness, Tendency